Optimalisasi Bimbingan Karir Dalam Proses Pengembangan Diri Penyandang Disabilitas Di Forum Komunikasi Disabilitas Kudus - Rahmawati, Heny Kristiana (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Optimizing Career Guidance in the Self-Development Process of Persons with Disabilities at the Kudus Disability Communication Forum .This study aims to obtain an in-depth description of the Implementation of Career Guidance, the efforts and obstacles in the Self-Development Process of Persons with Disabilities at the Kudus Disability Communication Forum. This study uses a qualitative approach that is presented descriptively with data collection techniques used through observation, interviews, and documentation of the activities in the Kudus Disability Communication Forum. In this study, it was found that the efforts of the FKDK were to establish relationships with social institutions so that they could develop and be accepted by the community, in addition to holding social activities to foster social feelings and empathy for fellow persons with disabilities. The obstacles experienced often come from within the individual, such as a lack of self-confidence and a willingness to grow. It is necessary to hold more training related to self-motivation, personal branding, and self-understanding in addition to developing and forming a high sense of self-esteem for people with disabilities, this is also a provision for people with disabilities.Keywords: Career Guidance, Self-Development, Disability